NIR-responsive metal-containing polymer hydrogel for light-controlled microvalve. Issue 23 (21st May 2021) - Lin, Xusheng; Xie, Weiwei; Lin, Qin; Cai, Yuanting; Hua, Yuhui; Lin, Jianfeng; He, Guomei; Chen, Jiangxi
Abstract : NIR-responsive metal-containing polymer hydrogel was prepared via the radical copolymerization of N -isopropylacrylamide and an osmium aromatic complex. It has excellent photothermal property and can be used as a light-controlled microvalve. Abstract : Metal-containing polymers have drawn considerable interest because of their unexpected and fantastic properties, and can be applied for preparing functional hydrogels. However, covalently cross-linked metal-containing polymer hydrogels have been rarely investigated due to the difficulty in incorporating metal centers into macromolecular networks. In this study, a functional metal-containing polymer hydrogel was prepared by covalently cross-linking N -isopropylacrylamide using a new metalla-aromatic complex as the cross-linking agent, based on which excellent photothermal properties are obtained under NIR laser irradiation. The phase transition can be reversibly controlled by the irradiation or nonirradiation of the NIR laser. This intelligent and controllable phase transition behavior can be applied to light-controlled hydrogel microvalves. The NIR light-responsive metal-containing polymer hydrogel represents a new smart hydrogel material.